2019
DOI: 10.37358/rc.19.6.7296
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin in the Treatment of Dyslipidemic Patients with Very High Cardiovascular Risk and Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is defined as the presence of hepatic fat accumulation after ruling out other causes of hepatic steatosis. The aim of the study is to identify the role of statin therapy in dyslipidemic patients with very high cardiovascular risk and NAFLD in achieving low density lipoprotein (LDL) cholesterol targets while also evaluating the changes in liver enzymes levels. This prospective study included 140 patients with NAFLD, hyperlipidemia and elevated cardiovascular risk. Serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Contrary to the PIVENS trial [33], treatment with atorvastatin and vitE alone did not improve ALT and AST. An improvement of AST and ALT was also reported for NAFLD patients receiving 20 mg atorvastatin for 12 weeks, with no additional effect by supplementing the statin with 400 IU vitE and 1000 mg vitC [32], whereas others have reported a reduction in ALT but not AST following six months of statin treatment (10–20 mg) in NAFLD patients [34]. The histological findings from the HF+ animals in the present study supports a state of hepatic stress, and show an increase NAS-score compared to LF and LF+ reaching significance at Week 28.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the PIVENS trial [33], treatment with atorvastatin and vitE alone did not improve ALT and AST. An improvement of AST and ALT was also reported for NAFLD patients receiving 20 mg atorvastatin for 12 weeks, with no additional effect by supplementing the statin with 400 IU vitE and 1000 mg vitC [32], whereas others have reported a reduction in ALT but not AST following six months of statin treatment (10–20 mg) in NAFLD patients [34]. The histological findings from the HF+ animals in the present study supports a state of hepatic stress, and show an increase NAS-score compared to LF and LF+ reaching significance at Week 28.…”
Section: Discussionmentioning
confidence: 99%
“…Although no therapy has yet been approved, vitE is recommended for NASH patients and is associated with improvements in histopathological lesions [31]. Alongside vitE supplementation, atorvastatin can be administered to target dyslipidemia in NASH patients and clinical studies have shown beneficial effects of statin treatment on dyslipidemia and markers of hepatic health in patients [32,33,34]. However, comparisons between studies are often challenging due to differences in, e.g., inclusion criterions and intervention time, dose and statin-type.…”
Section: Discussionmentioning
confidence: 99%